2014
DOI: 10.1097/ncq.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

Using Process Improvement Methodology to Address the Complex Issue of Falls in the Inpatient Setting

Abstract: Falls in the acute care hospital are a significant patient safety issue. The purpose of this article was to describe the use of process improvement methodology to address inpatient falls on 5 units. This initiative focused on a proactive approach to falls, identification of high-risk patients, and a complete assessment of patients at risk. During the project timeframe, the mean total fall rate decreased from 3.7 to 2.8 total falls per 1000 patient days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…38 The variable of male sex was not included in the simplified tool because sex was not reversible through fall prevention intervention. 4 Another reason sex was excluded was because nurses in the study hospital reported that they would feel awkward to conduct patient education when male sex was the only identified risk factor for falls.…”
Section: Discussionmentioning
confidence: 99%
“…38 The variable of male sex was not included in the simplified tool because sex was not reversible through fall prevention intervention. 4 Another reason sex was excluded was because nurses in the study hospital reported that they would feel awkward to conduct patient education when male sex was the only identified risk factor for falls.…”
Section: Discussionmentioning
confidence: 99%
“…Falls can result in patient injury and death (Christopher et al . ). They also place an increased economic burden on patients, their families and the health care system (Halfon et al .…”
Section: Introductionmentioning
confidence: 97%
“…Earlier studies demonstrated the utility of the Six Sigma approach on improving various processes in the healthcare sector, namely, surgery turnaround time (Adams et al , 2004), hospital discharge process (Vijay, 2014), hand hygiene compliance (Eldridge et al , 2006), antibiotic prophylaxis in surgery (Parker et al , 2007), scheduling radiology procedures (Volland, 2005), catheter-related bloodstream infections (Frankel et al , 2005), nosocomial urinary tract infections (Hansen, 2006) and internal processes in a hospital (De la Lama et al , 2013). A few studies have also addressed the application of Six Sigma approach in reducing the patients’ falls rate in hospitals (Goldsack et al , 2015; Christopher et al , 2014). This approach is executed in five phase, namely, defining opportunities (D); measuring performance (M); analyzing opportunities (A); improving existing performance (I); and control the improved performance (C).…”
Section: Introductionmentioning
confidence: 99%